Investigating the Effect of Various Fillers on Cohesive Failure Mechanism in Asphalt Mixtures - Hamedi, Gholam Hossein; Sohrabi, Mohsen; Sakanlou, Farhad; Tahami, Seyed Amid (Periodica Polytechnica Civil Engineering, 2020)
In the current research attempts have been made to investigate the effect of various fillers on the resistance to mastic failure using mechanical and thermodynamic methods. Two types of granite and limestone aggregates with acidic and basic characteristics were used, respectively. Besides, four types of filler including calcium carbonate, hydrated lime, Portland cement and stone powder and two types asphalt binder PEN 60-70 and PEN 85-100 were used. Calcium carbonate and hydrated lime had the most effect and Portland cement and stone powder had the least effect on strength reduction. In addition, the results obtained by modified Lottman test showed that the use of hydrated lime and calcium carbonate increased resistance to moisture damage. The results of correlation coefficients show the necessity of using the effect of filler on cohesion free energy calculation in the surface free energy to investigate cohesion failure in different asphalt mixtures.